Tools for ensuring digital quality of life of the population in the national economy - Mukhacheva Anna (π-Economy)
The relevance of the study is determined by the need to satisfy the vital, social and moral interests of the population through the use of information and communication technologies, i.e. the formation of a digital quality of life, in the context of the development of the digital economy and the data economy. The term “digital quality of life” remains conceptually and definitionally unexplored, and the foundations of its formation are still practically not considered by researchers. Digital technologies determine the development of education, healthcare, social protection, law enforcement, environmental safety, labor market, public consumption, and the implementation of social and spiritual needs. Digital twins act as a catalyst for territorial development in the digital world within the framework of ecosystem provision of quality of life. More and more examples of their effective application can be found in Russian regions and cities. At present, the state has developed many information and analytical systems, some of which can form elements of a single socio-economic digital space, a digital twin of the territory. Digitalization of the social ecosystem for ensuring quality of life also has disadvantages. Among them, it is worth noting the increasing speed of change in the modern VUCA world, previously unknown to man and capable of causing negative psychological states (stress, frustration, psychological disorders), as well as cyber risks associated with the possibility of malicious use of personal data, and the standardization of public life. At the same time, digitalization of the social sphere, economy and public life is an objective and inevitable reality, the advantages of which are significantly greater for maintaining the quality of life of the population, and the disadvantages can be leveled by the same digital tools and the proper degree of attention of state and municipal authorities. The purpose of the study is to develop the theoretical and conceptual foundations of the category “digital quality of life”, to determine the tools for its formation, development and assessment. Research objectives are as follows: to form the theoretical and conceptual foundations of the category “digital quality of life”; to develop framework groups of indicators for assessing the digital quality of life of the population; to analyze the implementation of digital tools for the implementation of various interests of citizens; to consider existing information and analytical systems for managing the digital quality of life of the population. The research methods are the standard methods of description, comparison, system analysis, synthesis, economic and statistical assessment, and study of research on the topic. The practical significance of the research results is the possibility of using recommendations for the formation of the digital quality of life of the population to increase the degree of satisfaction of various interests of citizens at the federal and regional levels.